Use of long-acting reversible contraceptives in the UK from 2004 to 2010: Analysis using The Health Improvement Network Database. (December 2014) - Cea Soriano, Lucía; Wallander, Mari-Ann; Andersson, Susan; Filonenko, Anna; García Rodríguez, Luis Alberto
Abstract: Objectives To determine the use of long-acting reversible contraceptives (LARCs) in the UK over the period 2004 to 2010, using the general practice database The Health Improvement Network (THIN). Methods Women in THIN, aged 18 to 44 years during 2004 to 2010, who had been registered with their general practitioner for at least five years, with a prescription history of at least one year were included. THIN was searched using the Read and MULTILEX codes for: copper intrauterine devices (Cu-IUDs), the levonorgestrel releasing-intrauterine system (LNG-IUS), progestogen-only implants, and progestogen-only injections. Results The prevalence of progestogen-only implant use rose from 0.5 to 3.4%, and that of the LNG-IUS from 3.1 to 5.2%. The annual incidence and prevalence of progestogen-only implant use increased for all age groups but was most marked in younger women, whereas the use of the LNG-IUS augmented with increasing age. For all women, there was a small decrease in the prevalence of use of Cu-IUDs (from 5.4 to 4.8%) and progestogen-only injections (from 3.6 to 3.2%). Conclusions Uptake of progestogen-only implants and the LNG-IUS increased over the period 2004 to 2010 in the UK, but LARC use in young women remains low. Chinese Abstract 摘要目的 通过全科数据库-健康促进网络数据库(THIN)明确2004至2010年间英国长效可逆避孕药(LARCs)的使用情况。 方法 研究纳入THIN数据库中, 在2004年至2010年年龄18至44周岁的女性，在其全科医生处登记至少五年，处方史至少一年。使用Read和MULTILEX代码在THIN中搜索：含铜宫内节育器(Cu-IUDs)，左炔诺孕酮宫内缓释系统(LNG-IUS)，单孕激素植入和单孕激素注射。 结果 单孕激素植入的使用率由0.5%升高到3.4%，LNG-IUS的使用率由3.1升高到5.2%。单孕激素植入的年新增使用率和使用率在所有年龄组中均上升，在年轻妇女中上升的最为明显, 而LNG-IUS的使用率随着年龄的增长而增加。 Cu-IUDs（5.4%到4.8%）和单孕激素注射(3.6%到3.2%)在整体人群中的使用率略有下降。 结论 2004年至2010年英国单孕激素注射和LNG-IUS使用率上升，但LARC在年轻妇女中的使用率仍保持低值。